HSP27 and HSP70 expression in squamous cell carcinoma: An immunohistochemical study - Parviz Deyhimi; Faezeh Azmoudeh (Wolters Kluwer Medknow Publications, 2012)
Background: Heat shock proteins (HSPs) are a family of proteins that are known to play a significant role in the repair of denatured proteins in the cell. It seems that cytoprotective properties of HSPs may help in malignant progression by facilitating tumor cell growth and survival. The purpose of this study is to evaluate HSP27 and HSP70 expression in various histopathological grades of squamous cell carcinoma (SCC). Materials and Methods: In this retrospective-analytical study, the sections of 51 formalin-fixed paraffin-embedded biopsy specimens of SCC from various sites of oral and paraoral regions and 10 normal oral mucosa were immunostained by Novolink Polymer technique to determine the expression of HSP27 and HSP70. Then the data were analyzed according to the Kruskal-Walis, Mann-Whitney and the Spearman correlation tests (P<0.05). Results: The expression of HSP27 in well-differentiated SCC was significantly higher than normal epithelium (P=0.007) and in moderately differentiated SCC higher than poorly-differentiated SCC (P=0.023). Inverse correlation was observed between HSP27 expression and SCC's histopathological grade (P=0.001, r=-0.448). There was no significant difference between HSP70 staining of specimens (P=0.38). Conclusions: The present study revealed that the expression level of HSP27 was inversely related to histopathological grade of SCC and it may provide prognostic value for patients with SCC, but there was no significant relationship between the expression of HSP70 and histopathological grades of SCC.